The Developmental Origins of Selective Social Learning - Poulin-Dubois, Diane (Curr Dir Psychol Sci, 2016)
The study of children's social learning is a topic of central importance to our understanding of human development. Learning from others allows children to acquire information efficiently; however, not all information conveyed by others is accurate or worth learning. A large body of research conducted over the past decade has shown that preschoolers learn selectively from some individuals over others. In the present article we summarize our work and that of others on the developmental origins of selective social learning during infancy. The results of these studies indicate that infants are sensitive to a number of cues, including competence, age, and confidence, when deciding from whom to learn. We highlight the important implications of this research in improving our understanding of the cognitive and social skills necessary for selective learning, and point out promising avenues for future research.